The use of mitomycin C with autologous limbal-conjunctival autograft transplantation for management of recurrent pterygium - Mohamed A Fakhry (Dove Medical Press, 2011)
Mohamed A FakhryDepartment of Ophthalmology, Kasr El Aini Hospital, Cairo University, Cairo, EgyptPurpose: The purpose of this study is to evaluate and compare recurrence rates upon using mitomycin C (MMC) with limbal-conjunctival autograft for treating recurrent pterygia.Methodology: An interventional, prospective, comparative clinical study was performed in 30 eyes (26 patients) with recurrent pterygia, allocated into two groups: Group A (19 eyes) operated by pterygium excision and limbal-conjunctival autograft transplantation (L-CAT) without MMC and Group B (20 eyes) operated with injection of 0.1 mL of MMC 0.15 mg/mL 1 month before L-CAT surgery. Exclusion criteria included patients with symblepharon, cicatricial conjunctival diseases, limbal stem cell deficiency, and other intraocular diseases.Results: A total of four cases of recurrences for Group A (P = 0.012) and one case of recurrence for Group B (P < 0.001) were recorded.Conclusions: Preoperative injection of MMC in low dose and concentration improves the results of L-CAT in recurrent pterygium.Keywords: recurrent pterygium, limbal autograft, conjunctival autograft, mitomycin C